2015
DOI: 10.1155/2015/373041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga on Utero-Fetal-Placental Circulation in High-Risk Pregnancy: A Randomized Controlled Trial

Abstract: Introduction. Impaired placentation and inadequate trophoblast invasion have been associated with the etiology of many pregnancy complications and have been correlated with the first trimester uterine artery resistance. Previous studies have shown the benefits of yoga in improving pregnancy outcomes and those of yogic visualization in revitalizing the human tissues. Methods. 59 high-risk pregnant women were randomized into yoga (n = 27) and control (n = 32) groups. The yoga group received standard care plus yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
(34 reference statements)
1
16
0
3
Order By: Relevance
“…The reviewers also concluded that yoga was a more effective exercise than walking or standard prenatal exercises. In a study on the effects of yoga on fetal growth measures and uterine artery resistance a yoga group was compared to a group who received standard care plus walking [40]. The yoga sessions were held three times a week for 1 h during the 12th to the 28th weeks of gestation.…”
Section: Beneficial Effectsmentioning
confidence: 99%
“…The reviewers also concluded that yoga was a more effective exercise than walking or standard prenatal exercises. In a study on the effects of yoga on fetal growth measures and uterine artery resistance a yoga group was compared to a group who received standard care plus walking [40]. The yoga sessions were held three times a week for 1 h during the 12th to the 28th weeks of gestation.…”
Section: Beneficial Effectsmentioning
confidence: 99%
“…Significantly fewer women in the yoga group developed a hypertensive disorder in the index pregnancy and had a lower rate of fetal growth restriction and Doppler changes. 19,27 The women in the yoga group also maintained normal uric acid and platelet levels throughout their pregnancy, thereby reducing the risk of developing hemolysis, elevated liver enzymes, low platelet count syndrome. 20 They also experienced a significantly lower degree ofstressandpregnancydiscomforts in pregnancy.…”
Section: High-risk Populationsmentioning
confidence: 99%
“…Several studies demonstrate higher birth weights and lower rates of fetal growth restriction in those who practice yoga in pregnancy. 8,27 It is conceivable to deducea positive impact ofyoga on the fetus Yoga in Pregnancy 11 www.clinicalobgyn.com exists;however,furtherstudiesareneededto confirm these conclusions.…”
Section: Risksmentioning
confidence: 99%
“…Rakhshani et al 20 published the first study to assess Doppler changes in a prenatal yoga study in 2015. Their RCT assessed uterine, umbilical, and fetal middle cerebral artery Doppler indices at the 12th, 20th, and 28th gestational week in 59 high-risk pregnant women who either practiced yoga 3 times/week or walked twice daily for 16 weeks.…”
Section: Commentmentioning
confidence: 99%